First Case Report of Familial Hypercholesterolemia in an Omani Family Due to Novel Mutation in the Low-Density Lipoprotein Receptor Gene. (May 2013) - Al-Hinai, Ali T.; Al-Abri, Abdulrahim; Al-Dhuhli, Humoud; Al-Waili, Khalid; Al-Sabti, Hilal; Al-Yaarubi, Saif; Al-Hashmi, Khamis; Banerjee, Yajnavalka; Al-Zakwani, Ibrahim; Al-Rasadi, Khalid
Familial hypercholesterolemia (FH) is an autosomal dominant genetic disorder. Mutations have been found in at least 3 genes: the low-density lipoprotein receptor ( LDLR ), apolipoprotein B ( APOB ), and proprotein convertase subtilisin/kexin type 9 ( PCSK9 ). We report the first case of FH in an Omani family due to a novel mutation in the LDLR gene. A 9-year-old female was referred to our lipid clinic with eye xanthelasmata and thickening of both Achilles tendons. Evaluation of the lipid profile showed the off treatment total cholesterol of 896 mg/dL (23.2 mmol/L), low-density lipoprotein cholesterol (LDL-C) of 853 mg/dL (22.1 mmol/L), APOB of 4.5 g/L, triglyceride of 71 mg/dL (0.8 mmol/L), and high-density lipoprotein cholesterol of 0.74 mmol/L. Genetic analysis of the LDLR gene showed a homozygous frameshift deletion mutation (272delG) at exon 3. The female patient was treated with a combination of rosuvastatin/ezetimibe and LDL apheresis.